Endothelial expression of fractalkine (CX3CL1) is induced by Toll-like receptor 3 signaling in cultured human glomerular endothelial cells. Issue 6 (1st November 2020) - Hirono, Koji; Imaizumi, Tadaatsu; Aizawa, Tomomi; Watanabe, Shojiro; Tsugawa, Koji; Shiratori, Toshihiro; Kawaguchi, Shogo; Seya, Kazuhiko; Matsumiya, Tomoh; Ito, Etsuro; Tanaka, Hiroshi
Abstract: Background: Endothelial expression of membrane-bound fractalkine/CX3CL1 (Fkn) reportedly acts as a strong mediator of inflammation. Toll-like receptor 3 (TLR3) axes are thought to play some roles in the development of chronic glomerulonephritis (CGN) including lupus nephritis (LN). However, detailed mechanism of TLR3-mediated Fkn expression in glomerular endothelial cells (GECs) remains to be elucidated. Methods: We examined the effect of polyinosinic–polycytidylic acid (poly IC) on Fkn expression in cultured human GECs. Fkn mRNA and protein levels were quantified by real-time PCR and enzyme-linked immunosorbent assay, respectively. To further elucidate the effects of poly IC on this signaling pathway, we used small-interfering RNA (siRNA) to knockdown expression of TLR3, nuclear factor (NF)-κB p65, interferon (IFN)-β, and IFN regulatory factor 3 (IRF3). We then analyzed whether pretreatment of chloroquine or dexamethasone (DEX) inhibits poly IC-induced Fkn expression. Results: We found that poly IC-induced Fkn expression in GECs, and that this involved NF-κB, IFN-β, and IRF3. Pretreating cells with chloroquine, but not DEX attenuated poly IC-induced Fkn expression in GECs. Conclusion: Since the activation of TLR3/NF-κB/IFN-β/Fkn and TLR3/IRF3/Fkn axes is involved in inflammatory reactions in GECs, intervention of glomerular TLR3 signaling may be a suitable therapeutic strategy for treating CGN especially LN.